Atividade antifúngica de óleos vegetais no controle de podridão-por-fusarium em melão e fusariose em abacaxi - Sousa, Aline Ellen Duarte de (Universidade Federal Rural do Semi-Árido, 2010)
The use of essential oils of medicinal plants has shown promising results in controlling plant pathogens, even though much of the Brazilian flora has not yet been studied. The discovery of new chemical compounds from plants that can control the development of plant pathogens is of great importance especially for use in post-harvest. The present study evaluated in vitro and in vivo, the effect of essential oils of rosemary-pepper (Lippia sidoides Cham.), Basil, clove (Ocimum gratissimum L.), Ocimum sp., Basil (Ocimum micranthum), paregoric (Ocimum selloi), orange (Citrus sinensis), pepper jack (Piper aducum) and grass (Cymbopogon citratus Stapf.), as alternatives for the control of diseases caused by Fusarium subglutinans and Fusarium pallidoroseum in melon and pineapple. In in vitro tests, the oils were added to PDA at concentrations of 0, 500, 1500 and 3000 mL L-1. We evaluated the mycelial growth of pathogens and spore germination. In in vivo tests, fruit were inoculated using a spore suspension and mycelial discs. After 24 hours, melon fruits were submerged in solutions of treatments for ten seconds. With the pineapple, the treatments were applied before and after inoculation as a preventive and curative treatment. In in vitro test, oils of lemongrass, rosemary, pepper, basil, clove and basil showed inhibitory potential on mycelial growth and spore germination of Fusarium pallidoroseum and F. subglutinans. In in vivo test all essential oils, in concentrations, caused burns and depressions in the melon. As a curative treatment of pineapple, the oils of rosemary-pepper and basil-clove at all concentrations completely controlled the incidence of F. subglutinans. As a preventive treatment, rosemary, pepper and basil were used. This control occurred at concentrations of 1500 mL L-1.
Antifungal activity of plant oils under rot control per fusarium in melon and fusariose in pineapple
Keywords: Fusarium pallidoroseum; Fusarium subglutinans; óleos essenciais; plantas medicinais; Fusarium pallidoroseum; Fusarium subglutinans; essential oils; medicinal plants; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA